The effect of abolishing university tuition costs: Evidence from Ireland - Kevin Denny (Institute for Fiscal Studies (IFS), 2011)
University tuition fees for undergraduates were abolished in Ireland in 1996. This paper examines the effect of this reform on the socio-economic gradient to determine whether the reform was successful in achieving its objective of promoting educational equality that is improving the chances of low socio-economic status (SES) students progressing to university. It finds that the reform clearly did not have that effect. It is also shown that the university/SES gradient can be explained by differential performance at second level. Students from white collar backgrounds do significantly better in their final second level exams than the children of blue-collar workers. The results are very similar to recent findings for the UK. The results show that the effect of SES on school performance is generally stronger for those at the lower end of the conditional distribution of academic attainment.
Keywords: I21; I22; 330; tuition costs; university; fees; socio-economic background; educational attainment